A Review on the Rasayanas (Rejuvenatives) from Chakradatta and Market Survey for the Availability of Rasayana Drugs and Formulations - Mahadar Sayali Pravin; Jamdade Yogita. A (International Journal of Ayurveda and Pharma Research, 2022)
Rasayana therapy is the essence of Ayurveda. It places great emphasis on prevention and encourages the maintenance of health through close attention to balance in one’s life. For achieving this state, Ayurveda encircles various approaches of assessment. Various Rasayanas are mentioned in Ayurveda compendiums. Chakradatta is one of the important compendia written by Chakrapani which is known as Chikitsasangraha wherein details about treatment methods are given. Details of Rasayan chapter of Chakradatta, and drugs/ formulations having ‘Rasayana’ word in their indications are reviewed in this article. After studies it is found that, 22 Rasayana drugs/ formulations are mentioned in the Rasayan chapter of Chakradatta, and 22 Rasayana drugs/ formulations are mentioned in overall text, apart from the Rasayan chapter of Chakradatta. A market survey was conducted in the area around the PDEA’s College of Ayurved and Research Centre, Nigdi, to find the availability of Rasayana drugs and formulations from Chakradatta. It was found that out of 51 raw drugs and formulations 40 are available in the market.